Gênero, divisão sexual do trabalho e empoderamento das mulheres no mundo do trabalho - Pereira, Telma Amélia de Souza (2022)
This article aims to reflect on the concepts of gender, sexual division of labor and empowerment. This text is part of the construction of the doctorate in Education. Through a bibliographic review, from a feminist studies perspective, highlighting the way in which the relations of domination imposed on women by men and how this same domination is presented factors that promote inequality, justified by the inferiorization of women, the perennial defense of patriarchal social roles remains. These situations push women away from certain areas of the world of work. Empowerment, thought in the sense of awareness of their social condition by women, is the possibility that can facilitate the reduction of the oppressions that are imposed by patriarchal society.